Analysing and evaluating a thermal management solution via heat pipes for lithium-ion batteries in electric vehicles - Wang, Qian (2015)
Thermal management is crucial in many engineering applications because it affects the electrical, material, and other properties of the system. A recent study focuses on the use of heat pipes for battery thermal management in electric vehicles, which explores a new area for heat pipe applications.